Strategi Hukum dalam Mengatasi Pelanggaran Hak Cipta di Industri Film Indonesia - Yusnani Afida; Romi Faslah (CV. ITTC INDONESIA, 2025)
Copyright infringement, especially in the form of movie piracy, is a serious threat to the growth of the film industry in Indonesia. Despite the existence of regulations governing copyright protection, such as Law Number 28 of 2014 on Copyright, piracy practices are still often found today, especially through digital platforms. This study aims to analyze the legal strategies applied in dealing with copyright infringement in the Indonesian film sector. The approach used is normative juridical with descriptive analysis method, based on the study of relevant laws and case studies. The results show that the legal strategy implemented still faces various challenges, including weak law enforcement, low public awareness, and limited supervision of illegal digital distribution. Therefore, an integrated effort is needed between the government, industry players, and law enforcement officials in strengthening copyright protection, both through improving regulations and public education.